The Effect of Work Discipline, Motivation, And Compensation on Employee Performance at CV. Diandra Putra Pratama Surabaya City - Riska Faulia Rahma; Jojok Dwiridotjahjono (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to examine the effects of work discipline, motivation, and compensation on employee performance at CV. Diandra Putra Pratama, Surabaya. An associative research design with a quantitative approach was utilized, employing a nonprobability sampling technique with saturated sampling. The sample consisted of 30 employees. Data analysis was conducted using multiple regression analysis. The findings indicate that work discipline, motivation, and compensation collectively have a significant impact on employee performance. However, when examined individually, only the motivation factor shows a significant positive effect on employee performance, whereas work discipline and compensation do not significantly influence employee performance.